(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The Present Study of the paper is an attempt to increase the socio-economic development of the country. The paper is written with the view that the political stability can go with economic or financial stability for socio-economic development of the country. The present work is an attempt to study the "Indian Planning and Economic Development Working of Finance Ministry ". Briefly, then, an attempt is made to analyze the retrospect and prospect factors of some major economic policies in India.